2019
DOI: 10.3390/ijms20184439
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Peptide Humanin Protects Silver Nanoparticles-Induced Neurotoxicity in Human Neuroblastoma Cancer Cells (SH-SY5Y)

Abstract: The extensive usage of silver nanoparticles (AgNPs) as medical products such as antimicrobial and anticancer agents has raised concerns about their harmful effects on human beings. AgNPs can potentially induce oxidative stress and apoptosis in cells. However, humanin (HN) is a small secreted peptide that has cytoprotective and neuroprotective cellular effects. The aim of this study was to assess the harmful effects of AgNPs on human neuroblastoma SH-SY5Y cells and also to investigate the protective effect of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 125 publications
(180 reference statements)
0
25
0
Order By: Relevance
“…To our knowledge, Hippo pathway sustained normal cellular functions to suppress cancer aggressiveness and development [29,30]. However, the normal cells acquired malignant phenotypes and turned into cancer cells when the Hippo pathway dysregulated [31,32], and recent publications reported that dysregulation of the Hippo pathway accelerated GC progression [33][34][35]. As previously described, the downstream Yes-associated protein 1 (YAP1) was proved as an oncogene to facilitate pathogenesis of multiple cancers [36], such as pancreatic cancer [37], lung cancer [38], and GC [39].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, Hippo pathway sustained normal cellular functions to suppress cancer aggressiveness and development [29,30]. However, the normal cells acquired malignant phenotypes and turned into cancer cells when the Hippo pathway dysregulated [31,32], and recent publications reported that dysregulation of the Hippo pathway accelerated GC progression [33][34][35]. As previously described, the downstream Yes-associated protein 1 (YAP1) was proved as an oncogene to facilitate pathogenesis of multiple cancers [36], such as pancreatic cancer [37], lung cancer [38], and GC [39].…”
Section: Introductionmentioning
confidence: 99%
“… Neuroblastoma cell line (SH-SY5Y). Human HN-silver Nanoparticles Neuroprotection [ 102 ] Alzheimer's disease Cortical neurons Rats HN Attenuation of NMDA- excitotoxicity, improvement of mitochondrial function [ 103 , 104 ] Alzheimer's disease Brain Mice HNG Improved cognitive function [ 105 , 106 ] Alzheimer's disease Brain Rats HNG Reversal of impairment of spatial memory [ 107 ] Alzheimer's disease Brain Mice HNG Decreased Aβ level and ameliorated cognitive impairment. [ 108 ] Alzheimer's disease Brain Rats HN Amelioration of memory deficits induced by Aβ (1-42).…”
Section: Multiple Functional Properties Of Humaninmentioning
confidence: 99%
“…Cellular mitochondrial oxidative capacity is correlated with the number and size of mitochondria [ 146 ]. The dysregulation of mitochondrial biogenesis and dynamics due to oxidative stress leads to a decrease in mtDNA copy number, mitochondrial number, mitochondrial mass and oxidative capacity [ 35 , 102 , 147 ]. Thus, enhanced mitochondrial biogenesis could be one of the mechanisms by which cells regulate mitochondrial bioenergetics.…”
Section: Hn Improves Mitochondrial Function In Rpe Cellsmentioning
confidence: 99%
See 2 more Smart Citations